Spare Parts Faculty Guide - K-State First (Kansas State University, K-State First., 2016)
This guide provides background knowledge related to "Spare Parts" by Joshua Davis and its topics for Kansas State University professors and faculty to use within their classes and on campus. Included in the guide are a timeline of the characters' lives, discussion questions, thematic information, similar titles, and on-campus resources.
Citation: K-State First (2016). Spare Parts Faculty Guide [Flier]. Manhattan, Kansas: K-State First.
Keywords: Spare Parts; Guide; Faculty development; Common reading program; First-year experience program; Application of learning; Fliers (printed matter)